ANALISA KAPASITAS BATERAI SEBAGAI SUMBER DC PADA GARDU INDUK TEGANGAN EKSTRA TINGGI 500 KV PT.PLN (PERSERO) TASIKMALAYA - Muhammad Farisha Istiqlal; Edvin Priatna; Sutisna Sutisna (Teknik Elektro Universitas Siliwangi, 2023)
The Batteries are very important to distribute DC current in a substation. If the battery is damaged and can no longer be used, it will affect the equipment or load it supplies, this can cause damage and disruption to the electric power distribution system. Therefore, this research and analysis was carried out to maintain high reliability and stability in the DC system at the 500 kV Extra High Voltage Substation PT.PLN (persero) Tasikmalaya. The DC system at this substation is connected in parallel with the rectifier and the load, so that if the AC source is interrupted, the battery will immediately take over the full role of supplying the load. The results of the analysis show that the DC source is very important for reliability at the substation, and periodic maintenance is needed to anticipate potential disturbances to the DC system and maintain battery performance. Periodic maintenance is also required to maintain the performance of critical control equipment and protection equipment.